2019
DOI: 10.7717/peerj.7408
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant gene and pathways involved in HBV-related hepatocellular carcinoma by bioinformatics analysis

Abstract: Background Hepatocellular carcinoma (HCC) is a common malignant tumor affecting the digestive system and causes serious financial burden worldwide. Hepatitis B virus (HBV) is the main causative agent of HCC in China. The present study aimed to investigate the potential mechanisms underlying HBV-related HCC and to identify core biomarkers by integrated bioinformatics analyses. Methods In the present study, HBV-related HCC GSE19665, GSE55092,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 62 publications
4
36
0
Order By: Relevance
“…FOXM1 contributes to multiple cancers by promoting cellular proliferation and tumor initiation via β-catenin and cyclin D1 (Kim et al, 2019;Shukla et al, 2019). Bioinformatics analysis showed that FOXM1 was also involved in the development of hepatitis B virus (HBV)-related HCC (Xie et al, 2019). Aberrant CENPA expression participates in multiple stages of cancer progression by regulating the cell cycle (Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 contributes to multiple cancers by promoting cellular proliferation and tumor initiation via β-catenin and cyclin D1 (Kim et al, 2019;Shukla et al, 2019). Bioinformatics analysis showed that FOXM1 was also involved in the development of hepatitis B virus (HBV)-related HCC (Xie et al, 2019). Aberrant CENPA expression participates in multiple stages of cancer progression by regulating the cell cycle (Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis shows that ANLN participates in HBV-related hepatocellular carcinoma. 25 Surveys such as that conducted by Dai et al show that ANLN down-regulation takes part in the prognostic of breast cancer survival by interacting with KDR. 26,27 ANLN overexpression leads to poor prognosis and poor clinical outcome to anthracycline-based chemotherapy in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Among these studies, integrative bioinformatics strategies have been employed to analyze the DEGs in a large number of tumor samples. For example, Xie et al, 8 analyzed four Gene Expression Omnibus (GEO) datasets including GSE19665, GSE55092, GSE94660, and GSE121248 and identified key genes and pathways involved in HBVrelated HCC. 8 Ma et al, 9 obtained the mRNA expression profiles from the GEO database and the Cancer Genome Atlas-Liver Hepatocellular Carcinoma database, and the results showed that eleven hub genes with the most interactions were suggested as potential biomarkers in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xie et al, 8 analyzed four Gene Expression Omnibus (GEO) datasets including GSE19665, GSE55092, GSE94660, and GSE121248 and identified key genes and pathways involved in HBVrelated HCC. 8 Ma et al, 9 obtained the mRNA expression profiles from the GEO database and the Cancer Genome Atlas-Liver Hepatocellular Carcinoma database, and the results showed that eleven hub genes with the most interactions were suggested as potential biomarkers in HCC. 9 Yan et al, 10 conducted a comprehensive study on bioinformatics, clinical analysis and in vitro validation and found that Misato family member 2, pseudogene had significant diagnostic and prognostic value in HCC.…”
Section: Introductionmentioning
confidence: 99%